A micromechanical model to study the closure stress effect on fatigue life of Ti6Al4V subjected to laser shock peening. (September 2018) - Luo, Y.J.; Chen, J.B.; Wang, X.F.; Zhao, Y.X.; Zhang, A.B.; Xie, C.; Chen, Y.; Du, J.K.
Highlights: The residual stress characteristics of LSPed Ti6Al4V is described. An extended N-R model incorporating closure stress effect is established for LSP. Effect of closure stress on fatigue crack propagation behavior is deeply analyzed. The fatigue life of LSPed Ti6Al4V is predicted. Abstract: With the wide application of titanium alloy in various engineering fields, the service life of Ti alloy product has drawn much more attention. It's been proven that the laser shock peening (LSP) is an effective technology to improve the fatigue performance of titanium alloy by introducing a large and deep compressive residual stress. In this paper, a microstructural fracture mechanics model incorporating the crack closure stress effect is presented to investigate the reinforcement mechanism of laser shock peened (LSPed) titanium alloy. Firstly, a rigid-plastic simplified model is utilized to describe the residual stress characteristics of LSPed Ti6Al4V. Then the extended Navarro-Rios model incorporating crack closure stress effect is established to systematically analyze the crack propagation behavior. Finally, the effect of crack closure stress on fatigue life can be accurately predicted. Result shows that the crack propagation processing is a behavior reflecting the deceleration and acceleration of the crack growth rate. A higher threshold stress is required for LSPed Ti6Al4V to promote the propagation of fatigue crack. The closure stress effect reduces the barrier stress and critical crack length in each grain leading to the highly raised fatigue life of LSPed Ti6Al4V. Besides, the closure stress effect has a greater improvement in fatigue performance for a sample with a shorter crack length and thus can be neglected for a long crack.